Organizational Conflict - Alice Vilas Boas, Ana (IntechOpen, 2018)
In this book, we learn about organizational conflict, highlighting different perspectives of conflict resolution and conflict management in different settings and areas, as well as different theoretical views on this subject. The authors from Norway, Estonia, Nigeria, Israel, USA, Slovakia, Turkey, Finland, Uruguay, and Italy bring ideas, studies, findings, and experiences to enhance our knowledge in the field of organizational conflict. The book is divided into two sections, and their respective chapters refer to two different perspectives of study. The first section covers Conceptual Frameworks on Organizational Conflict, considering management and conflict resolution, conflict in organizations as an indicator for organizational values, organizational trust as a conflict management tool, conflicts and social capital, and team conflict in complex adaptive systems. The second section deals with Empirical Studies on Organizational Conflict, emphasizing research on conflict resolution from the perspective of managers and project teams, resistance to change and conflict of interest, conflicts as a springboard for Metallica's success, drivers of innovation deployment affecting marketing relationships, and impacts of national culture on the use of bonuses for teamwork. Thus, we consider this book will be of interest to readers with a diverse group of interests in different specialties such as management, social psychology, education, law, and sociology.